Komponen gizi, aktivitas antioksidan dan karakteristik sensori bubuk fungsional labu kuning (Cucurbita moschata) dan tempe - Junita, Dini; Setiawan, Budi; Anwar, Faisal; Muhandri, Tjahja (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
The aim of this research was to determine the nutrient content, antioxidant activity and the sensory characteristics of functional powder from pumpkin (Cucurbita moschata) and tempeh. The formula was consists of 15% pumpkin flesh powder, 35% pumpkin seed powder, and 50% powder tempeh. The nutritional component was determined by proximate and spectrophotometric analysis, DPPH (2,2-diphenyl-1-picrylhidrazyl) assay for antioxidant activity, and the sensory characteristics was analyzed by 39 semi-trained panelists using 3 types of beverage i.e water, orange juice and milk. The results showed that the functional powder contained 6.84±0.09% moisture, 3.18±0.02% ash, 35.15±0.07% fat, 30.15±0.35% protein, 20.85±0.35% carbohydrate, 3.86±0.02% crude fiber, 308.85±0.55 ppm total carotene, 515.00 ppb chromium, and 4.59% total sugar. Antioxidant activity of functional powder was 6765.88 ppm. According to the panelists, orange juice has the best sensory characteristics. This functional powder qualified for diabetic, futhermore investigate needed to improve the sensory characteristics and nutritional interactions.